1997
DOI: 10.1088/0031-9155/42/8/005
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of microcalcifications in computed and screen-film mammography

Abstract: Due to the clinically and technically demanding nature of breast x-ray imaging, mammography still remains one of the few essentially film-based radiological imaging techniques in modern medical imaging. There are a range of possible benefits available if a practical and economical direct digital imaging technique can be introduced to routine clinical practice. There has been much debate regarding the minimum specification required for direct digital acquisition. One such direct digital system available is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 39 publications
0
32
0
3
Order By: Relevance
“…It is known from several studies that calcifications as small as 130 ”m are visible to the human eye [27,28]. With the decrease in pixel size in magnifications and the less attenuated dose (magnification views are obtained without a grid), there is much more information/photons per pixel in more pixels [29].…”
mentioning
confidence: 99%
“…It is known from several studies that calcifications as small as 130 ”m are visible to the human eye [27,28]. With the decrease in pixel size in magnifications and the less attenuated dose (magnification views are obtained without a grid), there is much more information/photons per pixel in more pixels [29].…”
mentioning
confidence: 99%
“…Diameters of the deposits varied between 0.2 and 1.0 mm in steps of 0.1 mm, based on the dimensions of calcium deposits found in breast cancer. [27][28][29][30] The volume magnetic susceptibility of each sphere was set to that of calcium phosphate (−11 × 10 −6 , dimensionless SI units), 23 while the value for the surrounding medium was set to the value for water, −9×10 −6 . 3D gradient echo MR magnitude and phase images were simulated separately.…”
Section: A Gradient Echo Magnitude and Phase Image Simulationsmentioning
confidence: 99%
“…For SF mammography, Desponds et al (1991) reported a minimum visible size in the range of 170-220 ÎŒm and Sabol et al (1993) observed a minimum detectable size of 200 ÎŒm. Cowen et al (1997) found that the minimum detectable size was 130 ÎŒm for both SF and CR mammography. Rong et al (2002) reported that the minimum visible sizes were 110 ÎŒm for SF and FP-based digital mammography and 123 ÎŒm for CR and CCD-based mammography.…”
Section: Introductionmentioning
confidence: 96%